Faktor-Faktor Yang Berhubungan Dengan Peran Keluarga Dalam Merawat Pasien Halusinasi di Poliklinik Rumah Sakit Jiwa dr. Samsi Jacobalis Daerah Provinsi Kepulauan Bangka Belitung Tahun 2024 - Uswatun Hasanah; Nurwijaya Fitri; Nova Mardiana (Jurnal Riset Multidisiplin Edukasi, 2025)
The role of the family is very important for people with mental disorders, one of which is in patients with sensory perception disorders: Hallucinations, because the family is the closest and most important person to optimize mental peace for people with mental disorders. The aim of this research is to find out what factors are related to the role of the family in treating hallucinatory patients at the Regional Mental Hospital Polyclinic, Dr. Samsi Jacobalis Bangka Belitung Islands Province in 2024. This research is quantitative research with a cross- sectional approach. The samples in this study were families of people with mental disorders who were recorded and registered as visiting the Polyclinic at the Regional Mental Hospital, dr. Samsi Jacobalis of Bangka Belitung Islands Province as many as 56 people. The results of this study concluded that the factors related to family roles were knowledge p-value (0.031), and the more dominant factors were family attitudes p-value 0.031 and POR 3.800. The conclusion of this research is that knowledge and attitudes are related to the role of the family in caring for hallucinatory patients at the Regional Mental Hospital Polyclinic, Dr. Samsi Jacobalis Bangka Belitung Islands Province in 2024. The suggestion from this research is that it is hoped that the results of this research will be used as literature and a reference to improve counseling and increase knowledge through education in the community from an early age about the importance of the role of the family in people with mental disorders who experience hallucinations because they really need the role and helping hand of the family.